Methodological approaches that facilitate the constant learning in nursing leadership - Ises Adriana Reis dos Santos; Simone Coelho Amestoy; Gilberto Tadeu Reis da Silva; Vânia Marli Schubert Backes; Patrícia Alves Galhardo Varanda; Camila Dourado Reis das Virgens (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To know the methodological approaches that facilitate the constant learning of leadership by undergraduate nursing students. Method: Qualitative research, of case study type, carried out with 26 nursing students from a federal public university in the Northeast Region. For the collection, the workshop technique was applied in July and December 2017, with two different groups. Analyzed with the support of content analysis and Nvivo®11 software. Interpreted with the theoretical contribution of Peter Senge. Results: They listed two codes, understood as, essential to the formation of leaders, emerging the categories: Adoption of a leadership style; Qualities and attributes of the leader; Methodological approaches that facilitate the constant learning of leadership. Final considerations: It was identified that the application of teaching techniques and strategies, brings students closer to the performance scenarios. It is necessary to offer more stimuli during training since there are shortages in teaching for the development of leadership.